TUTORING IN OPEN EDUCATION IN UKRAINE AS A FACTOR OF DEMOCRATIZATION - Nepyipa, Nataliia (SWorldJournal, 2025)
The article provides a theoretical substantiation of tutoring as a pedagogical practice and a mechanism for the democratization of higher education in Ukraine in the context of open education. The study highlights the relevance of rethinking the role of